Tribological Bench and Engine Dynamometer Tests of a Low Viscosity SAE 0W-16 Engine Oil Using a Combination of Ionic Liquid and ZDDP as Anti-Wear Additives - Barnhill, William C.; Gao, Hong; Kheireddin, Bassem; Papke, Brian L.; Luo, Huimin; West, Brian H.; Qu, Jun (Frontiers in Mechanical Engineering, 2015)
We have previously reported an oil-miscible phosphonium-organophosphate ionic liquid (IL) with effective anti-wear functionality when added to a base oil by itself or combined with a conventional zinc dialkyldithiophosphate (ZDDP) for a synergistic effect. In this research, we investigated whether this synergy manifests in formulated engine oils. An experimental SAE 0W-16 engine oil was generated using a combination of IL and ZDDP with equal phosphorus contribution. The prototype engine oil was first evaluated using tribological bench tests: anti-wear performance in boundary lubrication and friction behavior (Stribeck curves) in elastohydrodynamic, mixed, and boundary lubrication. The forthcoming standard Sequence VIE engine dynamometer test was then conducted to demonstrate improved fuel economy. Results were benchmarked against those of another experimental engine oil with almost the same formulation except using ZDDP only without the IL (similar total phosphorus content) and a baseline SAE 20W-30 engine oil. The IL-ZDDP formulation consistently outperformed the ZDDP-only formulation and the results from the bench and engine tests are well correlated.